ANALISA POTENSI WADUK RUKOH DALAM MEMENUHI KEBUTUHAN AIR DI KABUPATEN PIDIE, INDONESIAANALYSIS OF RUKOH RESERVOIR POTENCY FOR DETERMINING WATER REQUIREMENT IN PIDIE DISTRICT, INDONESIA - Siti Nurdhawata; Bambang Dwi Dasanto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2011)
Generally, reservoir can overcome problem of water availability in particular region. The reservoir collects excess water during rainy season to be used at the time of water shortage during dry season. In Pidie, the largest water sources are from Krueng Baro Geunik and Krueng Tiro. The reservoir is located at Krueng Rukoh with Krueng Tiro as the source of water supply. The reservoir provides water for irrigating and supplying domestic water in Baro (11.950 ha) and Tiro (6.330 ha) areas. There are 13 districts (216718 inhabitants) use the water from this reservoir. Given the population growing at rate of 0.52% then the water demand in the region increases. The aim of study was to estimate the volume of water entering the reservoir using the tank model. Calibration curve between the tank model output and observation data showed good correlation (R2 = 0.7). The calibrated model was then used to calculate the discharge at Krueng Baro Geunik. A water balance analysis showed that the highest deficit occurred in September and the highest surplus in November. Based on this analysis, the capacity of Krueng Rukoh reservoir is able to fulfill its function assuming the rate of population growth and the irrigation area are constant.